Media and information literacy - Zarate, Maria Jovita E. (Sampaloc, Manila : Rex Book Store, Inc., 2016)
"Media and Information Literacy charts an auspicious journey for the new generation of learners in the K to 12 program. The inclusion of a new course signifies the profound intent of the education reform to provide a coherent paradigm for a new generation of learners to actively engage in media and information. From this active engagement, the course hopes to introduce media and information literacy as fundamental tools for active citizens engagement. Each principle of media and information literacy bears a number of concepts that are defined and discussed in each chapter. These concepts are further operationalized using examples derived from the local scene, alerting learners to the moments that best illustrate the concepts. At the end of each chapter, culminating activities are presented to ensure students' learning."
Includes references.
English text.
Keywords: Media literacy; Information literacy